Perceptions and ideas of critically ill patients, their family and staff members regarding family participation in the physiotherapy-related care of critically ill patients: a qualitative study. (18th November 2022) - van Delft, Lotte; Valkenet, Karin; Slooter, Arjen; Veenhof, Cindy
ABSTRACT: Background: Involvement of families in physiotherapy-related tasks of critically ill patients could be beneficial for both patients and their family. Before designing an intervention regarding family participation in the physiotherapy-related care of critically ill patients, there is a need to investigate the opinions of critically ill patients, their family and staff members in detail. Objective: Exploring the perceptions of critically ill patients, their family and staff members regarding family participation in physiotherapy-related tasks of critically ill patients and the future intervention. Methods: A multicenter study with a qualitative design is presented. Semistructured interviews were conducted with critically ill patients, family and intensive care staff members, until theoretical saturation was reached. The conventional content method was used for data analyses. Results: Altogether 18 interviews were conducted between May 2019 and February 2020. In total, 22 participants were interviewed: four patients, five family members, and 13 ICU staff members. Six themes emerged: 1) prerequisites for family participation (e.g., permission and capability); 2) timing and interactive aspects of engaging family (e.g., communication); 3) eligibility of patients and family (e.g., first-degree relatives and spouses, and long stay patients); 4) suitability of physiotherapy-related tasks for family (e.g., passive, active and breathing exercises); 5) expected effects (e.g., physical recovery and psychological wellbeing); and 6) barriers and facilitators, which may affect the feasibility (e.g., safety, privacy, and responsibility). Conclusion: Patients, family members and staff members supported the idea of increased family participation in physiotherapy-related tasks and suggested components of an intervention. These findings are necessary to further design and investigate family participation in physiotherapy-related tasks.